Determination of oxygen ingress and carbon dioxide loss through plastic bottles using permeation simulation with hydrogen - Orzinski, Martin; Schneider, Jan; Hunger, Winfried (BrewingScience, 2007)
The beer and beverage industry is using ever more barrier enhanced plastic bottles for the filling of its products. The quality of the products can be considerably affected by the permeation of oxygen into the bottle and carbon dioxide out of it. The quality control of the bottles with particular emphasis on the gas barrier is thus of great importance. However, the conventional gas permeation measuring method needs too much time. In order to respond effectively and quickly to barrier defects, bottle production or incoming goods inspection measuring time must be shortened, for example by 2 hours. A physical problem of a quick measurement of oxygen is the comparably long unsteady state of permeation due to desorption of oxygen into the bottle after filling. Hydrogen as a test gas can overbear this difficulty because of its high molecular mobility and low viscosity so a method for the use of hydrogen was established. The ruggedness of the method meets the requirements of the practical measurement conditions. The correlation of the hydrogen ingress rate with the permeation coefficient of carbon dioxide and oxygen measured with a real-time method is not linear but can be used to differentiate between bottles with good or poor passive barriers. Active barriers employing scavenger material can not be detected by the hydrogen ingress measurement.